Cornelia Bryce Pinchot papers - Pinchot, Cornelia Bryce, 1881-1960.
Correspondence, journals, political campaign papers and speeches, book drafts, reports, notes, radio scripts, subject file, gardening file, financial records, press releases, printed matter, photographs, architectural and landscape plans, and other papers relating to her own campaigns as a candidate for U.S. Congress in 1928 and 1932; League of Women Voters; legislative efforts to protect women workers and children; the National Women's Trade Union League of America; Pinchot's activities as the wife of Gifford Pinchot, conservationist and governor of Pennsylvania; and women's suffrage.
Politician, political activist, and wife of Gifford Pinchot, conservationist and governor of Pennsylvania. Born Cornelia Elizabeth Bryce.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Pinchot, Gifford, -- 1865-1946.; United States. -- Congress -- Elections, 1928.; United States. -- Congress -- Elections, 1932.; League of Women Voters of Pennsylvania; National Women's Trade Union League of America; Children -- Legal status, laws, etc. -- United States; Gardening -- United States; Labor movement -- United States; Women -- Suffrage -- United States; Women -- Employment -- Law and legislation -- United States; Women political candidates -- Pennsylvania; Women labor union members -- United States; Pennsylvania -- Politics and government -- 1865-1950.; Governors' spouses; Politicians; Suffragists